2001
DOI: 10.1021/bi002681g
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Dynamic Perturbations Induced by Heme Binding in Cytochrome b5,

Abstract: The water-soluble domain of rat hepatic cytochrome b(5) undergoes marked structural changes upon heme removal. The solution structure of apocytochrome b(5) shows that the protein is partially folded in the absence of the heme group, exhibiting a stable module and a disordered heme-binding loop. The quality of the apoprotein structure in solution was improved with the use of heteronuclear NMR data. Backbone amide hydrogen exchange was studied to characterize cooperative units in the protein. It was found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 73 publications
5
46
0
Order By: Relevance
“…Interestingly, multiple sets of cross-peaks were detected for the Val 61b-Gly 62b-His 63b stretch, and this segment of the protein therefore adopted at least two conformations exchanging slowly on the chemical shift time scale. The chemical shifts for one of these conformations agreed well with those previously determined for apocytochrome b 5 (Falzone et al 2001), whereas the second set of observed chemical shifts differed by approximately 0.1 ppm.…”
Section: Resultssupporting
confidence: 85%
“…Interestingly, multiple sets of cross-peaks were detected for the Val 61b-Gly 62b-His 63b stretch, and this segment of the protein therefore adopted at least two conformations exchanging slowly on the chemical shift time scale. The chemical shifts for one of these conformations agreed well with those previously determined for apocytochrome b 5 (Falzone et al 2001), whereas the second set of observed chemical shifts differed by approximately 0.1 ppm.…”
Section: Resultssupporting
confidence: 85%
“…32 In addition, the replacements F35H and H39A occurred in folded regions of the apoprotein, as indicated by dipolar contacts placing Phe35 in the proximity of His39, Val45 and Tyr74. 19 The…”
Section: Choice Of Substitutionsmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18] The amino acid sequence of rat microsomal cyt b 5 is such that the apoprotein folds into a cooperative unit of marginal stability under physiological conditions of pH and temperature. 19 This unit comprises approximately two-thirds of the residues and corresponds closely to structural hydrophobic core 2 6 ; its DG8 of unfolding is 6 kJ mol 21 at 258C, 20 which implies that the apoprotein native state is 90% populated under those conditions. The $30 disordered residues are located in the heme binding site; once the cofactor binds, folding proceeds further, and cyt b 5 becomes a single all-encompassing cooperative unit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a substitute, the heme-binding loop of microsomal cytochrome b 5 (cyt b 5 ) (Fig. 2) has a suitable length (30-40 residues) and, in the apoprotein state, lacks predicted (Dunker et al 1998;Dosztanyi et al 2005) and observed (Falzone et al 1996;Bhattacharya et al 1999;Falzone et al 2001) rigid structure. In addition, a cellular environment does not force the loop to refold or collapse onto itself (Bryant et al 2005).…”
mentioning
confidence: 99%